Measles Surveillance Evaluation (Post Outbreak); Systems Approach at The Palu City Health Department In 2024 - Laba, Stefiani Bengan; Rau, Muhammad Jusman; Buchair, Nur Hikmah; Meliana, Relin; Royana, Nurul Vida (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Measles is an airborne disease with a very high transmission rate. There has been a global increase in both morbidity and mortality due to measles. In 2023, outbreaks occurred in several regions, particularly in Central Sulawesi, with Palu City being notably affected. This study aimed to evaluate the surveillance activities following the measles outbreak in the jurisdiction of the Palu City District Health Office, employing a systems approach. The research respondents included surveillance officers from the Palu City Health Office and those from the Puskesmas (community health centers) within its area. Data were collected through interviews and observations. The findings revealed several issues in the input aspect of surveillance, including overlapping roles for surveillance officers, a lack of knowledge transfer to new personnel, insufficient tactical funding for outbreak responses, and inadequate computer resources at some health centers to support surveillance activities. In the process aspect, challenges included the absence of designated contact persons from hospitals for all public health centers (PHCs), delays in the timely collection of zero case data, and inconsistent data processing with sub-district stratification among PHCs. Regarding the output aspect, reports were often not delivered promptly, and the dissemination of information was limited to internal stakeholders.